ANALYSIS OF VILLAGE GOVERNMENT PERFORMANCE IN PUBLIC SERVICES IN LATDALAM VILLAGE, SOUTH TANIMBAR DISTRICT, TANIMBAR ISLANDS REGENCY - Kusaly, Hartalena Efangelista; Aminah Bahasoan; Pieter Sammy Soselisa (PT. Banjarese Pacific Indonesia, 2024)
This study is a Qualitative Descriptive research aimed at analyzing the performance of the village government in providing public services in Latdalam Village, South Tanimbar District, Tanimbar Islands Regency, and analyzing the quality of public services in Latdalam Village, South Tanimbar District, Tanimbar Islands Regency. The research was conducted in Latdalam Village, South Tanimbar District, Tanimbar Islands Regency. Primary data collection was done through interviews with several informants including the village chief, village staff of Latdalam Village, South Tanimbar District, Tanimbar Islands Regency, and the local community. The research findings indicate that the services provided by the officials of Latdalam Village are still considered inadequate. Therefore, the Latdalam Village government needs to improve work discipline to ensure that future services provided to the community are better and more satisfactory.